DESIGN AND IMPLEMENTATION OF LIFEPO4 BATTERY STATE-OF- CHARGE MEASUREMENT, CURRENT AND TEMPERATURE SENSORS, AND CASING FOR ENERGIA: ENERGY MANAGEMENT SYSTEMS TO SUPPORT REMOTE LEARNING IN 3T REGIONS IN INDONESIA - William Hartono, Martinus
Despite rapid progress in the field of economic and technology development, Indonesia still has areas that are classified as 3T (frontier, remote, underdeveloped). On the other hand, with the advancement of digital technology, teaching and learning activities can be done anywhere through online media. However, not all students in the 3T area can access it due to limited access to electricity and internet. Therefore, Energia is designed as a solution which is an electrical energy management system for the generation and storage of renewable energy-based electrical energy. One of the important components in the system is the LiFePO4 battery. The remaining capacity in the battery needs to be monitored to prevent things that could harm the user and/or reduce the lifetime of the battery. These measurements can be expressed by State-of-Charge. In the implementation of the designed system, State-of-Charge is measured and calculated by measuring the open circuit voltage of the battery combined with the Coulomb Counting method. In addition, the measurement of current and temperature values is also designed with the help of a CD4052 multiplexer, and the system casing is designed to meet the IP33 Ingress Protection standard. In conclusion, it is found that the design has been successfully carried out, which is indicated by the measurement of State-of-Charge in an accurate open circuit condition, and Coulomb Counting which runs with a minor deviation of 1% measurement results. Current and temperature sensor data retrieval can be carried out properly, and the designed system casing meets the IP33 standard.